THE ANALYSIS OF ELLIPSIS AND SUBSTITUTION OF YOUTUBE ADVERTISEMENTS - Viatari Dipa Pencawan; Amrin Saragih (State University of Medan, 2015)
The study was deal with the types of ellipsis andsubstitution occurred intheutterances of Youtube Advertisements. The objectives of the study was toidentify and classify the types of ellipsis and substitution and explaining thereason why it becomes the dominant type that occurred in the advertisement. Thedata were analyzed by identifying the utterances found in thescript. The findingsshows that the three types of ellipsis and substitution are occurred in theadvertisement. The reason why it becomes the dominant type was because ellipsisand substitution can make an effective sentence which can be avoid the repetitionof words by omitting unnecessary words which can be predicted from the context.It also can make the sentence in the script more interesting.